The relation of spatial configuration in residential real estate towards its conduciveness security level - Ismihafizha, Hastya; Kusliansjah, Karyadi (Universitas Mercu Buana, 2024)
As a part of an area, residential real estate has various spatial configuration patterns, which are part of the elements that form its environment. Depending on the context of certain places, spatial configuration and security reinforcement become a concern regarding the issue of crime prevention, which promotes a safe neighbourhood that avoids the risk of crime. A phenomenon took place where there are several preventive actions were carried out at the basic stage of planning and designing residential real estate, but these efforts later brought various methods and priorities that determine spatial configuration or security reinforcement to serve either as the main reference or adjustment at the initial step. This research dissects the relationship between spatial configuration patterns and security systems applied using the Crime Prevention Through Environmental Design (CPTED) approach to obtain the most optimal solution in preventing crime and reducing crime rates. This research used descriptive analytical methods in a comparative way to derive the final synthesis of three residential real estates in Bintaro Jaya as study objects. The results of this research discovered the most conducive type of residential real estate in terms of its security level. These findings can enrich the development of studies on similar topics and contribute to the consideration of design criteria related to spatial configuration and security reinforcement of residential real estate in anticipating potential crimes.